2015
DOI: 10.1016/j.biocon.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Skin bacteria provide early protection for newly metamorphosed southern leopard frogs (Rana sphenocephala) against the frog-killing fungus, Batrachochytrium dendrobatidis

Abstract: 28An important concern for conservation biologists is the continuing loss of global biodiversity. 29 This is especially true for amphibians, which are disappearing at an alarming rate. The emerging 30 fungal pathogen, Batrachochytrium dendrobatidis (Bd), causes the skin disease chytridiomycosis 31 and is a major contributor to amphibian population declines. Recent studies suggest that 32 symbiotic skin bacteria provide some protection against Bd. Possible mitigation strategies 33 include skin microbiome manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 59 publications
2
46
5
Order By: Relevance
“…Much of the research pertaining to frog skin microbiota has focused on the complexities of the epidemic of chytrid fungus (Rollins-Smith et al, 2011;Jani & Briggs, 2014;Holden et al, 2015;Berger et al, 2016;Bates et al, 2018) and other frog skin diseases (Federici et al, 2015;Knutie et al, 2017), including suggestions of using probiotics on frog populations (Harris et al, 2009;Loudon et al, 2014;Küng et al, 2014) even at a landscape scale (Muletz, Myers, Domangue, Herrick, & Harris, 2012). These efforts have yielded inconclusive results, including problems associated with the resilience of the skin microbiota inhibiting the uptake of probiotics (Küng et al, 2014).…”
Section: Biologic Factors Include Transitions In Life Stagesmentioning
confidence: 99%
“…Much of the research pertaining to frog skin microbiota has focused on the complexities of the epidemic of chytrid fungus (Rollins-Smith et al, 2011;Jani & Briggs, 2014;Holden et al, 2015;Berger et al, 2016;Bates et al, 2018) and other frog skin diseases (Federici et al, 2015;Knutie et al, 2017), including suggestions of using probiotics on frog populations (Harris et al, 2009;Loudon et al, 2014;Küng et al, 2014) even at a landscape scale (Muletz, Myers, Domangue, Herrick, & Harris, 2012). These efforts have yielded inconclusive results, including problems associated with the resilience of the skin microbiota inhibiting the uptake of probiotics (Küng et al, 2014).…”
Section: Biologic Factors Include Transitions In Life Stagesmentioning
confidence: 99%
“…Amphibian skin bacterial communities may protect hosts against pathogens through several mechanisms including keystone species (Bletz et al., ), antagonistic interactions (Kueneman, Woodhams, Harris ; Kueneman, Woodhams, Van Treuren ) and biodiversity effects (Longo & Zamudio, ; Longo et al., ; Piovia‐Scott et al., ). Experimental data have shown that the reduction of bacteria via the application of antibiotics results in higher pathogen intensities (Holden et al., ). In addition, frogs with a particular community composition enriched with Flavobacteriaceae, Comamonadaceae and Pseudomonadaceae are better able to survive after infection (Becker et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that disruption of the microbiome of the cornea and conjunctiva may open a pathway for ocular disease (Abelson et al, 2015). Across diverse types of tissues, including the nose, gut, and skin, reductions in microbiome diversity have been associated with the development of and severity of infection (Chang et al, 2008, Biswas et al, 2015Holden et al, 2015;Sekirov et al, 2008). There are also numerous examples of resident microbiomes responding to pathogens (e.g.…”
Section: Introductionmentioning
confidence: 99%